Design and Build of Dacron Pillow Filling Machine to Increase Production Capacity and Reduce Production Costs - Carendy Indrawan; Murnawan, Hery (Tibuana, 2024)
This research was conducted at Mr. Khambali's SME. Mr. Khambali's pillow SME is engaged in producing pillows and bolsters with an average daily production of 140 units. The problemin Mr. Khambali's pillow SME is that the production output often does not meet demand because the process of stuffing the dacron into the pillow sack takes 8 minutes. This research aims to increase production capacity and reduce production costs. The method used in this research is Anthropometry, which is a reference for designing the machine to ensure its safe and comfortable use. Then, work time measurement is conducted using the time study method, and the calculation of production costs is compared before and after the design process. The results obtained from the design process are an increase in production from 140 units to 230 units per day and a reduction in production costs from IDR. 23,801 to IDR. 14,705. This research concludes that after designing the Dacron pillow-filling device, production increased by 90 units, and production costs decreased by IDR. 9,096.